2021
DOI: 10.1007/s10067-021-05952-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in children with juvenile systemic lupus erythematosus and ınvestigation of the possibly responsible factors

Abstract: Objective Insulin resistance (IR) has been described in adults with systemic lupus erythematosus (SLE), though its mechanism has not been fully clarified. In this study, it was aimed to investigate insulin sensitivity for the first time in children with juvenile SLE (jSLE) by considering the effect of the already known contributing factors of IR. Method This is a cross-sectional study including 43 patients with jSLE and the same number of healthy controls matched for age, gender, pubertal stage, body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our results may only reflect partial aspects of the HFD response in lupus. Lupus and obesity might be interconnected through other pathways to induce these immunological dysfunctions in HFD-associated lupus, such as proinflammatory soluble mediators generated by white adipose tissue,27 gut microbiota,28 29 oxidative stress,30 insulin resistance,31 increased body fat percentage and decreased muscle mass,32 oestrogen metabolism33 and vitamin D deficiency 34. Indeed, we found that serum MCP-1 level was significantly higher in the HFD group than the RD group, suggesting MCP-1 may play a role in HFD-associated lupus pathogenesis as observed in human patients with lupus by accelerating atherosclerosis and leading vascular damage (online supplemental figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…Our results may only reflect partial aspects of the HFD response in lupus. Lupus and obesity might be interconnected through other pathways to induce these immunological dysfunctions in HFD-associated lupus, such as proinflammatory soluble mediators generated by white adipose tissue,27 gut microbiota,28 29 oxidative stress,30 insulin resistance,31 increased body fat percentage and decreased muscle mass,32 oestrogen metabolism33 and vitamin D deficiency 34. Indeed, we found that serum MCP-1 level was significantly higher in the HFD group than the RD group, suggesting MCP-1 may play a role in HFD-associated lupus pathogenesis as observed in human patients with lupus by accelerating atherosclerosis and leading vascular damage (online supplemental figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to infections, SLE is associated with enhanced interferon secretion and insulin resistance. Compared to healthy controls, insulin resistance and the prevalence of metabolic syndrome, diabetes, and hypertension are higher in patients with SLE (adults and children) compared to healthy subjects [ 39 , 77 , 78 , 92 , 101 ]. Furthermore, the fasting plasma level of glucagon and the glucagon response to a meal tolerance test are increased in SLE patients compared to healthy subjects [ 77 ].…”
Section: Relationship Between Insulin Resistance and Apol1mentioning
confidence: 99%